PENGARUH PELAYANAN ASUHAN KESEHATAN GIGI DAN MULUT TERHADAP STATUS KESEHATAN GIGI DAN MULUT SISWA SD DI WILAYAH KERJA PUSKESMAS I DENPASAR SELATAN TAHUN 2011 - Ni made Sirat (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
Oral and dental diseases are commerly founds as a community diseases which are found in both children and adults since they affect deciduous as well as permanent teeth. Oral Health constitutes an integral part of health in general with important aspects in relation with the mastication, speech and esthetic functions. The objective of this research is to identify the impact of dental and oral health counseling service towards dental and oral health of elementary school students in the working area of community health center in south Denpasar in 2011.The design of this research is observational, cross sectional study. The sample are 128 persons, and in determining the samples the systematic random sampling was conducted. The result of this research shows that the counseling service has an impact to the OHI-S status with OR score of 9.930 and there is an impact between the counseling service and DMF-T status (p=0.000) with OR score of 5.942. Based on Chi Square test, it is found that the X2 value is X2 = 1.312 with p is at0.252 bigger that a=5% (0.2520.05). This shows that there is no impact between the knowledge of dental and oral health and OHI-S status of the students. There is no impact between the attitude and OHI-S status (p=0.120) and there is no impact between the attitude and the DMF-T status (p=0.209). There is an impact between the behavior and the DMF-T status of the elementary school students in the working area of Puskesmas in South Denpasar (p=0.001) with OR score of 5.800. The conclusion of this research is that in addition to the counseling service program, the behavior of the students also plays a significant role in the improvement of the dental and oral health of the elementary school students. It is suggested that dental health personnel in their dental and oral counseling service include not only the students and teachers but also the parents of the students as the persons who are closest to the students. In addition to that, the activities emphasize more on the promotional and preventive activities so that it can improve the level of the dental and oral health in order to prevent new carries.